Magnesium in pain control - mechanisms of action in perioperative pain, neuropathic pain and migraine - Anna Konarska; Artur Fabijański; Adriana Dukacz; Wojciech Firlej; Joanna Rychlewska-Duda; Justyna Lisiecka; Michał Nowak; Mateusz Janik; Barbara Ufnalska; Anna Machowiak (Journal of Education, Health and Sport)
Introduction